MATERNAL MORTALITY IN THE NATIONAL HOSPITAL EDGARDO REBAGLIATI MARTINS IPSS 25 YEARS EXPERIENCE - Pacheco Romero, José (2015)
In the first 25 years of existence of our Hospital there were 154 maternal deaths in women with an average of 31 years. 3.4 pregnancies, be hospitalized for labor (26%), induced by pregnancy (9%), septic abortion (12%) hypertensive disease. Direct obstetric causes accounted for 71.4% of deaths (110 cases), mainly due to infection (25.3%), hypertensive disease (21.4%) and hemorrhage (16.8%). Septic abortion and postpartum endometritis increased in the last 10 years of study. Indirect obstetric deaths (14.9%, 23 cases) were mainly due to pulmonary embolism, cardiovascular disorders and hepatic necrosis. And in non-obstetric deaths (13.6%, 21 cases) highlighted the processes and widespread lung infection. Our acceptable maternal mortality rate (48 per 100,000 live births) decreased from 78 in the first half to 41 in the last five years and was probably due to the best condition of the patient, proper medical satisfactory pre natal care and hospital resources.